Does Focal Osteolysis in a PRECICE Stryde Intramedullary Lengthening Nail Resolve after Explantation? - Oliver C. Sax; Larysa P. Hlukha; Kyle A. Kowalewski; John E. Herzenberg; Philip K. McClure (MDPI AG, 2022)
Concerns surrounding osteolysis near and around the modular junction of a stainless-steel intramedullary lengthening rod prompted a manufacturer recall from the United States market in early 2021. These actions were preceded by similar steps taken in Europe. A concomitant review of stainless-steel lengthenings at our institution demonstrated signs of adverse tissue reaction including periosteal reaction and osteolysis at the modular junction and/or male-sided locking screws. Nearly half of our patients presented with these findings on radiographic images. At the time of the previous review, only half of the nearly 60 implanted stainless-steel devices met a 6-month follow-up. At this juncture, many patients have had their devices explanted. Given the suspected adverse tissue reactions caused by a component of the internal device, we sought to examine the rate of osteolysis post-explantation following removal of a stainless-steel nail. We reviewed a consecutive series of patients who underwent implantation of a stainless-steel limb lengthening device in the femur and/or tibia at a single institution between December 2018 and December 2020. Patients were included if their device was explanted. Periosteal reaction and osteolysis was classified according to a novel and validated classification system, as analyzed by five fellowship-trained surgeons. In addition, changes observed prior to explantation were tracked post-explantation to assess for resolution. The incidence of periosteal reaction and osteolysis prior to explantation was 22/57 (39%) and 15/57 (26%), respectively. Of the 15 patients with osteolysis pre-explantation, 14 patients' implants were explanted. Of these, eight patients had available follow-up films. Two patients were identified as having partial osteolysis resolution at mean 1-year follow-up, while six patients were identified as having complete osteolysis at mean 18-months follow-up. Periosteal tissue reaction and osteolysis largely resolved following explantation in a subset of patients. These results provide further support to the claim that the stainless-steel device contributed to the changes seen. Further follow-up is warranted to examine the longer-term effects of adverse tissue reaction in this patient population.